2022
DOI: 10.1242/bio.059270
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting gestation periods in elasmobranch fishes

Abstract: Gestation periods vary greatly across elasmobranch species. Differences in body size and body temperature (i.e. major determinants of metabolic rates) might explain such variation. Although temperature effects have been demonstrated for captive animals, body size effects remain undocumented. Moreover, whether metabolic rates of mothers or those of embryos affect gestation periods remains unclear. Because biological times generally scale with mass1−β, where β is metabolic scaling exponent (0.8–0.9 in fishes), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, several studies have reported scaling exponents for various biological time periods, including gestation time, lactation (weaning) time, incubation time, age at maturity (first reproduction), and life span, that are significantly different from 1/4 [ 2 , 20 , 23 , 30 , 32 , 33 , 64 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ] or are curvilinear in log–log space [ 93 , 94 ]. In addition, mammalian life span shows a triangular pattern of covariation with body mass that is not adequately described by a single power function [ 64 , 84 , 87 , 90 ].…”
Section: Major Ways That Time May Be Relevant In Biological Scalingmentioning
confidence: 99%
“…Furthermore, several studies have reported scaling exponents for various biological time periods, including gestation time, lactation (weaning) time, incubation time, age at maturity (first reproduction), and life span, that are significantly different from 1/4 [ 2 , 20 , 23 , 30 , 32 , 33 , 64 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ] or are curvilinear in log–log space [ 93 , 94 ]. In addition, mammalian life span shows a triangular pattern of covariation with body mass that is not adequately described by a single power function [ 64 , 84 , 87 , 90 ].…”
Section: Major Ways That Time May Be Relevant In Biological Scalingmentioning
confidence: 99%
“…The first of these factors appears superficially similar to fecundity selection but differs in that it is the spatio‐temporal distribution of reproductive output rather than the magnitude of reproductive effort that differs between species. Selection for increased female size in matrotrophic shark species is logical given the number and size of pups produced and the extended gestation period of many sharks (Au et al., 2008 ; Tokunaga et al., 2022 ). Differences in the nature of sexual selection between oviparous and matrotrophic shark species are more problematic: in this study, we focused on testes mass—commonly used as a proxy for the intensity of post‐copulatory sexual selection, and failed to find any relationship between this variable and SSD (Tables 2 , 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…If females in NWA are copulating with multiple males to enhance offspring fitness, they may be extending individual mating windows to increase the likelihood of encountering fit males. Gestation lasts between 9-12 months and may be determined by water temperature for this species (Bennett and Bansemer, 2004;Tokunaga et al, 2022). Dispersal of pregnant females along the NC coast in varying depths likely means they may be experiencing a range of winter temperature regimes.…”
Section: Is Nc Important For Reproductive Ecology Of Sand Tigers?mentioning
confidence: 99%